Eurocon 2013 2013
DOI: 10.1109/eurocon.2013.6624999
|View full text |Cite
|
Sign up to set email alerts
|

Medium access control for thermal energy harvesting in advanced metering infrastructures

Abstract: In this paper we investigate the feasibility of powering wireless metering devices, namely heat cost allocators, by thermal energy harvested from radiators. The goal is to take a first step toward the realization of Energy-Harvesting Advanced Metering Infrastructures (EH-AMIs). While traditional batterypowered devices have a limited amount of energy, energy harvesting can potentially provide an infinite amount of energy for continuous operating lifetimes, thus reducing the cost involved in installation and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…ODMAC adjusts individually the duty cycle of each node, to the level that the energy consumed is at the same level of the energy harvested, thus maintaining it at state energy neutral. [36] is a first attempt to approach the energy harvesting WSNs in the metering industry by using the harvested thermal energy from radiators to power the nodes of the network (meters). Several are the contributions of this work: 1) to measure the energy harvested from the heat of a radiator, for which they developed a real prototype; 2) to compare analytically the default ALOHA-based MAC protocol typically used in the metering industry (IMR+) against ODMAC, the MAC scheme specifically designed for energy harvesting WSNs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…ODMAC adjusts individually the duty cycle of each node, to the level that the energy consumed is at the same level of the energy harvested, thus maintaining it at state energy neutral. [36] is a first attempt to approach the energy harvesting WSNs in the metering industry by using the harvested thermal energy from radiators to power the nodes of the network (meters). Several are the contributions of this work: 1) to measure the energy harvested from the heat of a radiator, for which they developed a real prototype; 2) to compare analytically the default ALOHA-based MAC protocol typically used in the metering industry (IMR+) against ODMAC, the MAC scheme specifically designed for energy harvesting WSNs.…”
Section: Related Workmentioning
confidence: 99%
“…Each sensor has a different opportunity for scavenging and different scheduling plans with a consumption and a quality associated to its service level. Differently to the works presented by other authors to provide energy-neutral operation in energy harvesting WSNs [7,15,25,26,36], our focus is to maximize the quality of the applications executed on each node of the network, where quality is a wider concept than the performance network, for which we provide a variety of scheduling plans that can be dynamically selected for execution.…”
Section: Related Workmentioning
confidence: 99%
“…Table II summarises Based on the presented analysis, it can be concluded that the maximum number of iterations in the case of ADMM could be configured to match the application requirements. For applications where data is transmitted only occasionally, such as smart metering systems where a single packet is sent once in 24 hours [23], T max can be set to a value much larger than 1000, potentially increasing the probability of packet correction. 1 The projection algorithm implementation for the ADMM decoder was taken from [22].…”
Section: Complexity Analysismentioning
confidence: 99%
“…However, TEGs have a low conversion efficiency under small temperature changes, and they are difficult to combine with MEMS technologies due to their construction and size. 7,8 A commercial TEG was reported in previous works, [53][54][55][56] as shown in Figure 8(a). Losada et al 56 demonstrated a wireless sensor device powered by a TEG for infrastructure health monitoring applications.…”
Section: Thermal Energymentioning
confidence: 99%
“…Peak power (20 mW) was generated at temperature gradient of 20 K. A TEG-based multiple sensor node for an aircraft health monitoring system was presented in previous works. 55,56 Continuous power of 200 mW was generated by the TEG under normal working conditions, as shown in Figure 8(b).…”
Section: Thermal Energymentioning
confidence: 99%